Desain Badan Peradilan Khusus Pemilihan Pasca Putusan Mahkamah Konstitusi Nomor 97/PUU-XI/2013 - Supriyadi Supriyadi; Aminuddin Kasim (The Constitutional Court of the Republic of Indonesia, 2020)
The Constitutional Court Decision Number 97 / PUU-XI / 2013 is a constitutional affirmation of the Court to relinquish its authority to resolve disputes over the results of regional head and deputy regional head elections. Given that conceptually the elections for regional heads and deputy regional heads are not included in the general election regime. After the decision of the Constitutional Court was issued Law Number 1 of 2015 as amended several times, most recently by Law Number 6 of 2020 which explicitly regulates and mandates the establishment of a special judicial body to handle disputes over election results. Neither the Constitutional Court decisions nor the Laws explain in detail the design of a special court that deals with disputes over election results. Therefore, this paper intends to answer research questions about; first, if the Constitutional Court has put the authority to resolve the election result dispute, what is the direction of the Constitutional Court’s thought in designing the settlement of the election result dispute based on decision Number 97/PUU-XI/2013? Second, the Constitutional Court Decision has been enumerated into the Election Law, is it in line with the Constitutional Court’s thoughts in the decision Number 97/PUU-XI/2013 with the normalization in the Election Law regarding disputes over results? third, how is the design of a special judicial body in line with the decision Number 97/PUU-XI/2013 and the Election Law? The research method used in this research is normative research with a statutory approach, conceptual approach, and case approach, with sources of literature law and prescriptive analysis techniques. The findings of this study are; First, the Decidendi Ratio of the Constitutional Court decision Number 97/ PUU-XI/2013 seems to implicitly place the authority to resolve disputes over the results of the elections as part of the authority of the Supreme Court. Second, the normalization of the Pilkada Law related to the settlement of election result disputes is in line with the Constitutional Court’s decision. Third, the design of a special electoral judiciary body is formed under the Supreme Court.